Until You Are Dead, Dead, Dead : The Hanging of Albert Edwin Batson - Bradshaw, Jim, 1944- (Book collections on Project MUSE., 2014)
In 1902, on a prairie in southwest Louisiana, six members of a farming family are found murdered. Albert Edwin Batson, a white, itinerant farm worker, rapidly descends from likely suspect to likely lynching victim as people in the surrounding countryside lusted for vengeance. In a territory where the locals were coping with the opening of the prairies by the railroad and the disorienting, disruptive advances of the rice and oil industries into what was predominantly cattle country, Batson, an outsider, made an ideal scapegoat. Until You Are Dead, Dead, Dead tells the story of the lega.